(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
This study examined the level of e-learning system among government and private schools and about the factor which are the causes of the difference in the level of e-learning system. The literature on E-learning system has clarified that these factors play an important role in the level of e-learning system.This study aimed to know the level of e-learning system among the secondary schools. The tool which was used in the study is highly reliable. The level of e-learning system was calculated. The result showed that these was no difference in the level of e-learning system but there was difference in the level of e-learning system due to the type of school.